MATERIALS FOR TEACHING CULTURE: LITERATURE, NEWSPAPERS, TV, INTERNET, PICTURES - Egamberdiyeva Irodaxon; Qodirov Xalilullo Raxmatullo o’g’li; Mahmudjonova Muxlisa Inomjon qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: Along with its intrinsic value, culture provides important social and economic benefits. With improved learning and health, increased tolerance, and opportunities to come together with others, culture enhances our quality of life and increases overall well-being for both individuals and communities. Below we will talk about how important newspapers, literature, TV, internet, pictures are in our study of culture.